ENGLISH LANGUAGE LEARNING STRATEGIES: AN EXPLORATORY STUDY OF MANAGEMENT AND ENGINEERING STUDENTS - Berlinda Mandasari; Lulud Oktaviani (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
Learning English as a foreign language, especially in a formal context, leads the students to have their own strategy in order to achieve the objective of learning. The strategy is considered as a helpful way to learn English better. After all, every student has their own strategy in learning. Thus, this study presents an exploration of English language learning strategies used by management and engineering students of Universitas Teknokrat Indonesia (UTI). Subjects of the research were 70 students who take English for Business (EFB) subject majoring management and engineering study program. Data were collected through questionnaire and interview. Data were then analyzed by using descriptive analysis. The result of this study gained a platform of learning strategies used by students. As a result, Management and Engineering students showed almost the same strategy in learning English in a class.